In the kingdom of the blind: successfully implementing institutional repositories in the UK and the SHERPA Partnership experience - Johnson, Gareth J (Taylor & Francis, 2007)
This paper takes an overview of the work of SHERPA team and the SHERPA Partnership institutions in the area of developing, populating and maintaining institutional open access repositories. Crucial to this work has been the development of mutually supporting and enabling Partnership community, something which has been now recognised as needed by institutions who lie outside of it. To this end SHERPA is involved in efforts to support the individuals and institutions across the UK and Europe whom are engaging with the open access agenda on a practical level; through setting up community networks and disseminating experience. Key in the experience of the Partnership has been the role of advocacy of open access and repositories to the institutional research community. Whilst this experience has been unique to each institution, there are many shared lessons and best practice that the Partnership has recently reflected on, and that are articulated within this paper. Finally brief coverage on some of the vital community tools developed and maintained by SHERPA, and reflections on the evolving direction of open access in the UK are made.